MEMAHAMI PENDIDIKAN AGAMA ISLAM MELALUI PROGRAM ADIWIYATA (CINTA LINGKUNGAN) DI SMP NEGERI 2 LAMONGAN - Hayyan Ahmad Ulul Albab (JP : JURNAL PENDIDIKAN, 2017)
Adiwiyata is a good and ideal place where all science, norms and ethics can be found in it. It will be the basis of human being towards the creation of life's prosperity and toward the ideals of sustainable development. In Indonesia, the total forest area currently reaches 124 million hectares. But from 2010 to 2015, the ranks of Indonesian’s forest is second highest loss of forest area and reaching 684,000 hectares per year. Islamic religious education is the process of transforming knowledge, Islamic values to learners through the efforts of teaching, habituation, guidance, upbringing, supervision and direction in order to achieve harmony and perfection of life in the world and the Hereafter. The first question, how is the concept of Islamic Religious Education through environmental education program Adiwiyata. The second question. What are the Supporting Factors and Inhibitors of Islamic Religious Education through Adiwiyata environmental education program and how is to Overcome Factors inhibiting in Islamic Religious Education through Adiwiyata environ-mental education program.Key words: Adiwiyata, Islamic Education and Environtment